Analisis Motivasi dan Reward Terhadap Kinerja Karyawan Pada PT. Nusantara Surya Sakti Kelapa Dua Tangerang - Adimas Ramadhan Suryanto; Iwan Asmadi; Tri Lestari (STIKes Ibnu Sina Ajibarang, 2023)
This research is related to the analysis of motivation and rewards on employee work performance at PT Nusantara Surya Sakti Kelapa Dua Tangerang. The purpose of this study is to determine the development of employee performance through the provision of motivation and rewards, because the role of employees in generating performance is very influential for the development of the company, proper work motivation and reward will increase the sense of responsibility of employees towards the company, work enthusiasm, and can complete tasks within the time specified by the company. This type of research uses quantitative research with non-statistical methods. The technique used for data collection in this study used a total sampling technique with an interview instrument distributed to respondents. The results of this study indicate that motivation and reward have a positive impact on improving the quality of employee work, companies need human resources to maintain the stability of the company by maintaining and developing employee performance.